Применение экономнолегированных сталей для деталей, работающих в условиях абразивного износа и термоциклических нагрузок - Панченко, Анна Николаевна; Сусло, Наталия Валериевна; Иванов, Андрей Сергеевич (НТУ "ХПИ", 2015)
Изложены результаты исследования возможности замены дорогостоящих высоколегированных хромоникелевых сталей для деталей, работающих в сложных термоциклических условиях и действии абразивного износа экономнолегированными безникелевыми сталями. Предложено легирование этих сталей марганцем и азотом взамен никеля для получения однофазной аустенитной структуры. При определении необходимого количества азота, учтена его растворимость в экономнолегированной стали, которая составляет 0,37 %, что позволяет получить в предлагаемой стали аустенитную структуру.

In the metallurgical production such as roasting of pellets and caking of agglomerate on conveyor type machines refer to thermal cyclic recurrence processes. At the same time the working bodies of conveyor machines are experiencing not only the impact of high cyclically varying temperatures, but and abrasion wear particles of the material being processed. Therefore, for the manufacture of structural assemblies of these machines use expensive steel containing from 2 to 12% nickel and 22-28% chromium. Despite the high content of alloying elements such as chromium and nickel components of longevity of these steels is 6-8 months, resulting in a reduction of technical and economic performance of the conveyor maсhine. The article presents the results of a study the possibility of replacing expensive high alloying chromium-nickel steels for components operating in thermal cyclic recurrence load and actions abrasion sparingly nickel-free steels. Proposed doping of manganese steel instead of nickel and nitrogen to produce a single-phase austenitic structure. When determining the required amount of nitrogen taken into account its solubility in sparingly alloyed steels which is 0.37%, which allows to obtain in the proposed austenitic steel structure.
The use sparingly alloyed steels for parts operating under abrasive wear and thermal cyclic recurrence load
Keywords: металлургическое производство; легирование; окатыши; аустенитная структура; economical alloyed steel; alloying; abrasion; pellets; austenitic structure